The Relationship between Safety Leadership Style and Safety Climate in Phosphoric Acid Industry - Dayinta Annisa Syaiful; Endang Dwiyanti (Universitas Airlangga, 2022)
Introduction: Phosphoric acid companies have risks that can lead to work accidents. There are several factors that influence the occurrence of work accidents, one of which is organizational and management factors. Leadership style is a factor in the work safety climate which leads to work accidents and work productivity. The purpose of this study was to analyze the relationship between leadership style and work safety climate in the Phosphoric Acid Plant at Phosphoric Acid Industry. Methods: The type of this research is descriptive quantitative research and through a cross-sectional approach to 44 workers at the Phosphoric Acid Plant. The variables of this study including safety leadership style and work safety climate. The data collection method used was secondary data obtained from the company’s annual data and as well as the primary data using the Leader Behavior Description Questionnaire and the Nordic Safety Climate Questionnaire. Each variable dimension was analyzed using the Spearman correlation method. Results: The results indicate that most workers, 47.7%, have both very high consideration and high initiating structure leadership style level. There is a relationship between leadership style and work safety climate with a correlation coefficient of 0.787 and shows a strong positive correlation. Conclusion: There is a strong positive relationship between leadership style and safety climate.